2022
DOI: 10.3390/polym14245367
|View full text |Cite
|
Sign up to set email alerts
|

Raman Study of Block Copolymers of Methyl Ethylene Phosphate with Caprolactone and L-lactide

Abstract: We present an in-depth analysis of Raman spectra of novel block copolymers of methyl ethylene phosphate (MeOEP) with caprolactone (CL) and L-lactide (LA), recorded with the excitation wavelengths of 532 and 785 nm. The experimental peak positions, relative intensities and profiles of the poly(methyl ethylene phosphate) (PMeOEP), polycaprolactone (PCL) and poly(L-lactide) (PLA) bands in the spectra of the copolymers and in the spectra of the PMeOEP, PCL and PLA homopolymers turn out to be very similar. This cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…PE is frequently used for manufacturing zip lock bags, bottles, food containers, food crates, stretch film, tape, pallets and plastic sheeting (Figure 1). The papers selected from the conference present widely varying types of polymers, such as polyurethane (PU) [9], cross-linked polyethylene (XLPE) [10], polycaprolactone (PCL) [11] and poly(L-lactide) (PLA) [11,12], microcapsules synthesized by the in situ polymerisation of crystal violet lactone (CVL), bisphenol A (BPA) and tetradecanol [13], polypropylene (PP) [14], and poly(3-hexylthiophene) [15]. In the following paragraphs, a concise overview of the published articles is provided in order to attract the interest of potential readers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PE is frequently used for manufacturing zip lock bags, bottles, food containers, food crates, stretch film, tape, pallets and plastic sheeting (Figure 1). The papers selected from the conference present widely varying types of polymers, such as polyurethane (PU) [9], cross-linked polyethylene (XLPE) [10], polycaprolactone (PCL) [11] and poly(L-lactide) (PLA) [11,12], microcapsules synthesized by the in situ polymerisation of crystal violet lactone (CVL), bisphenol A (BPA) and tetradecanol [13], polypropylene (PP) [14], and poly(3-hexylthiophene) [15]. In the following paragraphs, a concise overview of the published articles is provided in order to attract the interest of potential readers.…”
mentioning
confidence: 99%
“…It is also being evaluated as a material for tissue engineering; loose-fill packaging, compost bags, food packaging, and disposable tableware. New block copolymers of methyl ethylene phosphate (MeOEP) with caprolactone (CL) and L-lactide (LA) were examined via Raman spectroscopy [11]. An analysis of the peak positions, relative intensities and profiles of the poly(methyl ethylene phosphate) (PMeOEP), PCL and PLA bands showed that the conformational and phase compositions of each constituent in the copolymers did not differ significantly from those of the homopolymers.…”
mentioning
confidence: 99%